Exploring excited states of transition metal photocatalysts with time dependent density functional theory - Nite, Collette M., author; Rappé, Anthony K., advisor; Shores, Matthew, committee member; Strauss, Steven, committee member; Sites, James, committee member (Colorado State University. Libraries, 2018)
Advances in photocatalysis have led to a rise in interests in more sustainable chemistry. It has been shown that visible light can be harnessed through a photocatalyst to promote conventionally unfavorable chemical transformations. Most of these photoreactions rely on a rare metal photocomplex such as Ru(bpy)32+. However, in order to scale these reactions for industrial purposes, rare metals must be replaced with more earth abundant metals. First row transition metals provide an earth abundant alternative that open up new reaction pathways. Due to the differences between first and second and third row transition metals, catalytic design requires complex knowledge of the photophysics and photochemistry of the complex that is not easily obtained with experimental methods. Electronic structure methods can aid in catalytic design. Density functional theory (DFT) and time dependent density functional theory (TDDFT) are methods capable of calculating large molecular systems. TDDFT is a useful tool in studying excited states, providing excited state energies and intensities, probing the photochemistry of the system. However, DFT/TDDFT are by no means black box calculations, especially when calculating first row transition metal complexes with complicated spin state manifolds. Screening different metal ligand scaffolds requires a high level of benchmarking, ensuring functionals and basis sets are optimal for the given system. A higher level of analysis is required in order to go beyond the electronic spectrum to get at the vibronic character of a system. There is also a coupling between the protonation of a complex and the electronic excited state. Understanding the protonation effects of a system is very useful for tuning a catalyst to a given reaction. In addition, specific binding effects of a solvent must be understood in order to corroborate theoretical and experimental data. All of these factors must be considered when studying the character of metals and their relation to their ligand backbone. This dissertation highlights these issues associated with using TDDFT for photocatalytic development, and derives useful conclusions furthering the development of a first row transition metal photocatalyst.